Kritik Terhadap Cara Memuji Peserta kompetisi Hafiz Indonesia: Kontekstualisasi Hadis tentang Larangan Memuji - Muhammad Atiq (Alif Lam: Journal of Islamic Studies and Humanities, 2022)
Talking about praise, then the problem cannot be separated from the greatness and excellence of a person. In Islam, giving praise for one's superiority is not prohibited, even the Prophet SAW. often also praise his friends. However, there are limitations that need to be considered, if praising will cause ujub and arrogance in the person being praised then this is prohibited in Islam. The purpose of writing this article is to find out the hadiths about the prohibition of praising, holistic studies, hadith messages, and their implementation in the Hafiz Indonesia competition organized by the RCTI program. The existence of a hadith regarding the prohibition of excessive praise should be applied in the program so that participants and their families who take part in the competition avoid being arrogant and arrogant.